2018
DOI: 10.1007/s42399-018-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Uddanam Kidney Nephropathy Under the Light of Metagenomics Perspective

Abstract: In this work, we proposed a research hypothesis which mainly focuses on the role of gut microbiota, in relation with chronic kidney disease, existing in the village of Uddanam belonging to the State of Andhra Pradesh, India. Earlier studies conducted on various physical and chemical parameters, such as food, water, soil and pesticides, could not find the exact cause of the aetiology of the disease. As there were no physical and chemical causative factors identified, this disease was hence named as mysterious U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Data related to the cause of ESRD reported at the state hospital in Ede land revealed that over 13700 cases of hypertension, diabetes, and some infections were reported between 2007 and 2014 (8). According to Gross, Azevedo, and Silveiro diabetic nephropathy is the leading cause of chronic kidney disease in patients starting renal replacement therapy and it is associated with increased cardiovascular mortality (9)(10)(11)(12). Also, reported in their study that hypertension is the second leading cause of chronic kidney disease in all developed and many developing countries but glomerulonephritis and unknown causes are more common in countries of Asia and sub-Saharan Africa (SSA) (1,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Data related to the cause of ESRD reported at the state hospital in Ede land revealed that over 13700 cases of hypertension, diabetes, and some infections were reported between 2007 and 2014 (8). According to Gross, Azevedo, and Silveiro diabetic nephropathy is the leading cause of chronic kidney disease in patients starting renal replacement therapy and it is associated with increased cardiovascular mortality (9)(10)(11)(12). Also, reported in their study that hypertension is the second leading cause of chronic kidney disease in all developed and many developing countries but glomerulonephritis and unknown causes are more common in countries of Asia and sub-Saharan Africa (SSA) (1,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%